2019
DOI: 10.1002/brb3.1339
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of omega‐3 fatty acids on spinal cord injury induced rats

Abstract: Introduction In this study, the effects of omega‐3 fatty acids were examined in a rat model of spinal cord injury. Methods The rats were classified into sham, control, spinal cord injury plus 50 mg/kg Omega‐3 fatty acids and spinal cord injury plus 100 mg/kg Omega‐3 fatty acids. The levels of oxidative, apoptotic, and inflammatory markers were examined in each of these groups. Results Altered lipid peroxidation, reduced glutathione (GSH), sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…It results in inhibiting the phenomenon of the depolarization-induced increased activation of glutamate receptors [ 43 ]. Similar results concerning the anti-inflammatory activity of ω -3 acids were obtained by Bi et al [ 45 ], who noted a statistically significant ( p < 0.05) decrease in the concentrations of proinflammatory IL-6, interleukin 1 receptor antagonist (IL-1ra), C-reactive protein, and TNF- α in rats with SCI which were fed with food containing ω -3 acids. The concentration of anti-inflammatory interleukin 10 (IL-10) was directly proportional to the ω -3/ ω -6 acid ratio [ 43 ].…”
Section: The Biological Effect Of ω -3 Acids Insupporting
confidence: 86%
“…It results in inhibiting the phenomenon of the depolarization-induced increased activation of glutamate receptors [ 43 ]. Similar results concerning the anti-inflammatory activity of ω -3 acids were obtained by Bi et al [ 45 ], who noted a statistically significant ( p < 0.05) decrease in the concentrations of proinflammatory IL-6, interleukin 1 receptor antagonist (IL-1ra), C-reactive protein, and TNF- α in rats with SCI which were fed with food containing ω -3 acids. The concentration of anti-inflammatory interleukin 10 (IL-10) was directly proportional to the ω -3/ ω -6 acid ratio [ 43 ].…”
Section: The Biological Effect Of ω -3 Acids Insupporting
confidence: 86%
“…The results confirmed that when ω-3 PUFA (4 g/kg) was administered once, it revealed a protective effect against uremic toxin in the hippocampus region. Furthermore, in the brain of the spinal cord injury model wherein ω-3 PUFA was administered orally, the mRNA expression of apoptotic markers such as Bcl2, Bax, and caspase-3 was decreased [25]. The results of this paper show that ω-3 PUFA plays a protective role against oxidative stress and neuronal cell apoptosis caused by uremic toxins.…”
Section: Discussionmentioning
confidence: 62%
“…As summarized in the introduction, a dietary supplementation with n-3 fatty acids seems to be beneficial. In a rat model of spinal cord injury, dietary supplementation with DHA or EPA normalized lipid peroxidation, normalized the low level of glutathione and increased the activity of the superoxide dismutase, glutathione peroxidase and catalase enzymes [52]. Moreover, in an in vitro assay of rat primary astrocytes exposed to oxidative stress (H 2 O 2 ), both n-3 PUFAs concentration-dependently increased the level of glutathione and increased the levels of the NRF2-target genes [53].…”
Section: Discussionmentioning
confidence: 96%